Acceptability factors for wildlife approach in park and protected area settings. (15th May 2021) - Freeman, Stephanie; Taff, B. Derrick; Miller, Zachary D.; Benfield, Jacob A.; Newman, Peter
Abstract: Human-wildlife conflicts are a challenge in parks and protected areas around the world. Facilitating quality wildlife viewing experiences that minimize negative impacts to people and animals is often complicated by distance-related human behaviors. The purpose of this study was to examine how people's distance-related norms varied as a function of proximity from wildlife, wildlife species, and physical landscape features. By using virtual reality technology and simulations, this study assessed how physical landscape features (i.e., an open field, deadfall, and a paved road) impact wildlife viewing norms and also compared norms among three different wildlife species (i.e., bison, bear, and elk). Data were analyzed with repeated measures ANOVA to explore how these factors influenced acceptability ratings of distances between people and wildlife. Results revealed a significant interaction between distance to wildlife and landscape features. Recommendations for improving the management of humanwildlife conflicts and future research directions are discussed. Highlights: Acceptability of proximity to wildlife decreased as distance to wildlife decreased. Once physical landscape features no longer provided a barrier, proximity to wildlife became unacceptable. Wildlife species type did not impact acceptability of proximity to wildlife.